A bio-inspired approach for data dissemination in wireless sensor networks - Palafox-Maestre, Luis Enrique; Garcia-Macias, José Antonio (INFOCOMP Journal of Computer Science, 2006)
Recently, biologically-inspired algorithms have been presented as an alternative for designing many aspects of wireless ad-hoc and sensor networks. In this paper, we propose the adaptation of a bioinspired algorithm called the "infection algorithm" for the energy-efficient dissemination of data from a sensor field to the sink node. Furthermore, we present a series of experiments with real data, gathered through the use of an agriculturalmonitoring application, and also simulations that validate the efficiency of our proposal.